Circulating Levels of Hormones, Lipids, and Immune Mediators in Post-Traumatic Stress Disorder – A 3-Month Follow-Up Study - Jergović, Mladen; Bendelja, Krešo; Savić Mlakar, Ana; Vojvoda, Valerija; Aberle, Neda; Jovanovic, Tanja; Rabatić, Sabina; Sabioncello, Ante; Vidović, Anđelko (Frontiers in Psychiatry, 2015)
A number of peripheral blood analytes have been proposed as potential biomarkers of posttraumatic stress disorder (PTSD). Few studies have investigated whether observed changes in biomarkers persist over time. The aim of this study was to investigate the association of combat-related chronic PTSD with a wide array of putative PTSD biomarkers and to determine reliability of the measurements, i.e. correlations over time. Croatian combat veterans with chronic PTSD (n=69) and age-matched healthy controls (n=32), all men, were assessed at two time points separated by three months. Serum levels of lipids, cortisol, dehydroepiandrosterone-sulfate (DHEA-S), prolactin, and CRP were determined. Multiplex assay was used for the simultaneous assessment of 13 analytes in sera: cytokines (IFN-γ, IL-1ß, IL-2, IL-4, IL-6, TNF-α), adhesion molecules (sPECAM-1, sICAM-1), chemokines (IL-8 and MIP-1α), sCD40L, NGF, and leptin. Group differences and changes over time were tested by parametric or nonparametric tests, including repeated measures analysis of covariance. Reliability estimates (intraclass correlation coefficient (ICC) and kappa) were also calculated. Robust associations of PTSD with higher levels of DHEA-S (F(1,75)= 8.14, p=0.006)) and lower levels of prolactin (F(1,75)=5.40, p=0.023) were found. Measurements showed good to excellent reproducibility (DHEA-S, ICC=0.50; prolactin, ICC=0.79). Serum lipids did not differ between groups but significant increase of LDL-C after three months was observed in the PTSD group (t=6.87, p<0.001). IL-8 was lower in the PTSD group (t=4.37, p<0.001) but assessments showed poor reproducibility (ICC=-0.08). Stable DHEA-S and prolactin changes highlight their potential to be reliable markers of PTSD. Change in lipid profiles after three months suggests that PTSD patients may be more prone to hyperlipidemia. High intra-individual variability in some variables emphasizes the importance of longitudinal studies in investigations of PTSD biomarkers.